2014
DOI: 10.4149/neo_2014_057
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA mutations are a predictor of docetaxel plus epirubicin neoadjuvant chemotherapy clinical efficacy in breast cancer

Abstract: This study proposed to investigate the relationship of PIK3CA somatic mutations, the most common activating mutations in human breast cancer (BC), and the efficacy of neoadjuvant chemotherapy (NCT).Using a novel liquidchip technology, PIK3CA DNA somat ic mutations and HER2, PTEN, EGFR mRNA expression profiles were analyzed in formalin fixed paraffin embedded samples of 93 BC patients treated with epirubicin plus docetaxel NCT.PIK3CA mutations were found in 30 patients (32.3%), in which the point mutations of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…As shown in Table , 20 studies including 4392 patients were included in our meta‐analysis . Overall, PIK3CA mutation incidence in our meta‐analysis was 22.4% (range 7.7–39.0%).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As shown in Table , 20 studies including 4392 patients were included in our meta‐analysis . Overall, PIK3CA mutation incidence in our meta‐analysis was 22.4% (range 7.7–39.0%).…”
Section: Resultsmentioning
confidence: 98%
“…pCR was 28% for PIK3CA MT and 38% for PIK3CA WT. Seven studies were conducted in the United States, nine in Europe, and four in Asia . Two studies included objective response rate, while the others reported pCR as the endpoint in WT versus MT PIK3CA tumors.…”
Section: Resultsmentioning
confidence: 99%
“…However, PTEN gene expression was categorized only as up- or downregulated in this microarray analysis, with no further quantification [30]. Another study found PTEN gene expression to be significantly higher in 93 human breast cancer samples as compared to healthy breast tissue; however, the potential impact on survival was not assessed [31]. …”
Section: Discussionmentioning
confidence: 99%
“…As the time at which the Indian summer monsoon (ISM) starts can directly affect agriculture, the economy, and society in general, it is important to understand the onset of the summer monsoon (Moon & Ha, 2017;Ueda et al, 2015;Webster et al, 1998;Zhang et al, 2014). The social impact of not only the monsoon but also the start date is severe, especially in populated regions (Moon & Ha, 2017;Turner & Annamalai, 2012;Webster et al, 1998;Zhang et al, 2014). Note that the relationship between the monsoon rainfall rate and early monsoon onset is not linear (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%